Amelia Bedelia, bookworm - Parish, Herman (New York : HarperCollins, 2005)
The literal-minded housekeeper causes chaos at her local library when she stops by to help the librarian.
Keywords: Amelia-Bedelia (Fictitious character) -- Juvenile fiction; Miscommunication -- Juvenile fiction; Libraries -- Juvenile fiction; Humorous stories; Amelia-Bedelia (Fictitious character) -- Fiction; Miscommunication -- Fiction; Libraries -- Fiction